Universal synthesis method and application of medium-entropy / high-entropy alloy nanoparticles
A simple and efficient synthesis method was developed to prepare medium-entropy/high-entropy alloy nanoparticles, which solved the problems of harsh synthesis conditions and poor scalability in existing technologies. This method achieves uniform distribution and high-efficiency electrocatalytic performance of multi-component alloy nanoparticles, making them suitable for hydrogen evolution reaction in water electrolysis.
Patent Information
- Application Number
- CN202511020918.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-11-07
AI Technical Summary
Existing methods for preparing multi-component medium-entropy/high-entropy alloy nanoparticles suffer from problems such as harsh synthesis conditions, high cost, poor scalability, difficulty in particle size control, and uneven element distribution. There is a lack of universal, efficient, and scalable preparation strategies.
A general method for synthesizing medium-entropy/high-entropy alloy nanoparticles is adopted, which includes dissolving a metal precursor salt in deionized water, adding polyvinylpyrrolidone as a stabilizer, slowly adding sodium borohydride solution as a reducing agent to form a nanoparticle colloid, and obtaining alloy nanoparticles by centrifugation and vacuum freeze-drying.
The synthesis is mild and controllable, applicable to various ternary and pentaneous metal nanoalloys, exhibiting good crystallinity and uniform component distribution, demonstrating excellent electrocatalytic activity and durability, and suitable for hydrogen evolution reaction by water electrolysis.
Smart Images

Figure CN120901278A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of nanomaterials and electrocatalysis. Specifically, it relates to a synthesis method of medium entropy / high entropy alloy nanoparticles and its application; more specifically, it relates to a general synthesis method of medium entropy / high entropy alloy nanoparticles and its application in water electrolysis hydrogen evolution reaction. BACKGROUND
[0002] Hydrogen energy, as a new generation of clean energy carrier, has important significance in alleviating environmental pollution and achieving carbon neutralization. Water electrolysis hydrogen production technology is attracting attention due to its green and renewable nature, and the hydrogen evolution reaction (HER) is a key half-reaction in this process, and its energy efficiency directly determines the overall performance of the system.
[0003] Currently, the mainstream HER catalyst is still represented by platinum, which has excellent electrocatalytic performance, but its cost is high and its reserves are scarce, which limits its popularization and application in large-scale hydrogen production devices. In recent years, multi-component medium entropy alloys (MEAs) and high entropy alloys (HEAs) have attracted widespread attention in the field of electrocatalysis due to their unique multi-element synergistic effect, high structural stability, and flexible performance regulation characteristics.
[0004] High entropy alloys generally refer to solid solution structure materials composed of five or more metals, with the mole fraction of any component between 5% and 35%. They have high configurational entropy, which is conducive to the formation of stable single-phase structures. In addition, HEA nanomaterials can provide multiple active sites in the HER reaction, optimize the d-orbital center, and improve the catalytic activity.
[0005] However, the current methods for preparing such multi-component alloy nanoparticles still have many shortcomings, such as harsh synthesis conditions, high cost, poor scalability, difficulty in controlling particle size, uneven element distribution, and other issues. There is still a lack of a universal, efficient, and scalable preparation strategy.
[0006] Therefore, developing a universal synthesis method for medium entropy / high entropy alloy nanocatalysts has important scientific and industrial significance. SUMMARY
[0007] The first technical problem to be solved by the present application is to provide a universal synthesis method of medium-entropy / high-entropy alloy nanoparticles. The preparation method is suitable for synthesizing various ternary, quaternary and more than quaternary metal nano-alloys, especially suitable for medium-entropy and high-entropy systems; the obtained nanoparticles have good crystallinity, uniform component distribution and excellent structural stability; the preparation method does not require high temperature and high pressure conditions, the reaction temperature is less than 90℃, the process is simple and controllable; at the same time, the synthesis raw materials are easy to obtain, the synthesis path is simple, and it has the potential for large-scale production.
[0008] The second technical problem to be solved by the present application is to provide the application of the medium-entropy / high-entropy alloy nanoparticles prepared by the above preparation method in the hydrogen evolution reaction of water electrolysis. The medium-entropy / high-entropy alloy nanoparticles described in the present application exhibit low overpotential (<30mV@10mA / cm 2 ) and excellent durability in HER.
[0009] To solve the first technical problem, the present application adopts the technical solutions as follows :
[0010] A universal synthesis method of medium-entropy / high-entropy alloy nanoparticles comprises the following steps:
[0011] 1) Dissolve three or more metal precursor salts in deionized water according to the required molar ratio, and ultrasonic treat until completely dissolved to obtain a metal precursor solution A;
[0012] 2) Add polyvinylpyrrolidone as a stabilizer to solution A and stir uniformly;
[0013] 3) Slowly add 0.3-0.5M sodium borohydride solution as a reducing agent to solution A under stirring to form a reaction liquid B;
[0014] 4) React the reaction liquid B at 60-80℃ for 4-5 hours to form a uniform nanoparticle colloid;
[0015] 5) Centrifuge the nanoparticle colloid, wash 3-5 times with an equal volume of anhydrous ethanol and deionized water mixture, remove impurities, and vacuum freeze-dry for 8-12 hours to obtain black powder alloy nanoparticles.
[0016] Preferably, in step 1), the ultrasonic treatment time is 30-60min.
[0017] Preferably, in step 1), the required molar ratio refers to a molar ratio of 5-40%.
[0018] Preferably, in step 1), the metal precursor salt includes at least three of platinum salt, copper salt, silver salt, cobalt salt, nickel salt, and zinc salt.
[0019] Preferably, in step 1), the platinum salt is K2PtCl4; the palladium salt is K2PdCl4; the copper salt is CuCl2; the silver salt is AgNO3; the cobalt salt is CoCl2; the nickel salt is NiCl2; and the zinc salt is ZnCl2.
[0020] Preferably, the medium-entropy or high-entropy alloy nanoparticles include, but are not limited to, PtCuAg, PtCoNi, PtCoNiCu, PtPdCuAgZn.
[0021] Preferably, in step 2), the concentration of polyvinylpyrrolidone is 1-5 mg / mL.
[0022] Preferably, in step 3), the dropwise addition rate of sodium borohydride is 0.5-1 mL / min.
[0023] Preferably, in step 5), the centrifugation speed is 7000-9000 rpm, and the time is 8-12 min.
[0024] To solve the second technical problem, the present application adopts the technical solutions as follows :
[0025] Application of the medium-entropy / high-entropy alloy nanoparticles prepared by the above preparation method in the hydrogen evolution reaction of water electrolysis.
[0026] Preferably, the evaluation method of the catalytic performance of the medium-entropy / high-entropy alloy nanoparticles in the hydrogen evolution reaction of water electrolysis comprises the following steps:
[0027] 1) Catalyst ink preparation:
[0028] The alloy nanoparticles are dispersed in a mixed solvent of isopropyl alcohol and water, and an appropriate amount of Nafion (5 wt.%) is added as a binder, and ultrasonic treatment is performed to form a uniform catalyst ink;
[0029] 2) Electrode preparation:
[0030] The catalyst ink is drop-casted on a clean and dry carbon paper or glassy carbon electrode, and a working electrode is formed after drying;
[0031] 3) Electrochemical test:
[0032] In N2-saturated 0.5M H2SO4 or 1.0M KOH electrolyte, a three-electrode system (Hg / HgO or Hg / Hg2SO4, platinum wire as the counter electrode, and the working electrode as the alloy-loaded electrode) is used for linear sweep voltammetry (LSV), chronoamperometry (E-t), electrochemical impedance spectroscopy (EIS), and other performance tests.
[0033] Any range recited in the present disclosure includes the end values and any numerical value between the end values and any sub-range consisting of any such numerical values.
[0034] Unless otherwise specified, each raw material in the present application can be obtained by commercial purchase, and the equipment used in the present application can adopt the conventional equipment in the field or refer to the prior art in the field.
[0035] Compared with the prior art, the present application has the following beneficial effects :
[0036] 1) Strong universality: the method is suitable for synthesizing various ternary, quaternary and more than quinary metal nanometer alloys, and is particularly suitable for medium entropy and high entropy systems.
[0037] 2) Mild synthesis: no high temperature and high pressure conditions are required, the reaction temperature is < 90℃, the process is simple and controllable.
[0038] 3) Excellent structure: the obtained alloy has small particle size, narrow distribution, clear crystal structure and high uniform distribution of metal components.
[0039] 4) High catalytic performance: it shows low overpotential (< 30mV@10mA / cm 2 ), high quality activity and excellent durability in HER.
[0040] 5) Low cost: the synthesis raw materials are easy to obtain, and the synthesis path is simple, which has the potential for large-scale production. BRIEF DESCRIPTION OF DRAWINGS
[0041] The specific embodiments of the present application will be further described in detail below with reference to the accompanying drawings
[0042] Figure 1 is the TEM image and diffraction pattern of the high-entropy alloy nanoparticle electrocatalyst prepared in Example 1;
[0043] Figure 2 is the high-resolution EDS element mapping of the high-entropy alloy nanoparticle electrocatalyst prepared in Example 1;
[0044] Figure 3 is the XRD pattern and XPS pattern of the high-entropy alloy nanoparticle prepared by the preparation method of the present embodiment 1;
[0045] Figure 4 is the electrochemical performance (linear sweep voltammetry curve of hydrogen evolution reaction under acidic conditions) of the electrocatalyst and Pt / C prepared by the preparation method of the present embodiment 1;
[0046] Figure 5 is the LSV graph before and after 10000 cv cycles of stability test;
[0047] Figure 6 is the XRD pattern of the PtCuAg medium-entropy alloy nanoparticle prepared in Example 2;
[0048] Figure 7 Figure 7 is a high resolution EDS elemental mapping of the alloy catalyst prepared in Example 2, showing the highly uniform distribution of Pt, Cu and Ag in the particles;
[0049] Figure 8 Figure 8 is a transmission electron microscope (TEM) image of the alloy prepared in Example 2;
[0050] Figure 9 Figure 9 is an XRD pattern of the PtCoNiCu alloy nanoparticles prepared in Example 3, showing that it is a single-phase FCC structure;
[0051] Figure 10 Figure 10 is a transmission electron microscope (TEM) image of the PtCoNiCu alloy nanoparticles prepared in Example 3;
[0052] Figure 11 Figure 11 is an EDS elemental mapping of the alloy particles of the PtCoNiCu alloy nanoparticles prepared in Example 3;
[0053] Figure 12 Figure 12 is a comparison of the electrochemical performance (linear sweep voltammetry curves of hydrogen evolution reaction under acidic conditions) of the electrocatalysts prepared in Comparative Examples 1-4;
[0054] Figure 13 Figure 13 is a transmission electron microscope (TEM) image of the PtCoNiCuAg alloy nanoparticles prepared in Comparative Example 1;
[0055] Figure 14 Figure 14 is an XRD pattern and a transmission electron microscope (TEM) image of the PtCoNiCuAg alloy nanoparticles prepared in Comparative Example 4. DETAILED DESCRIPTION
[0056] In order to more clearly illustrate the application, the following further describes the application with reference to the preferred embodiments and the accompanying drawings. Like reference numerals in the drawings denote like elements. It should be understood by those skilled in the art that the following detailed description is illustrative rather than restrictive and should not be construed as limiting the scope of the application.
[0057] Various cross-sectional views according to the disclosed embodiments of the application are shown in the drawings. These views are not drawn to scale, in which certain details are exaggerated for clarity and others are omitted. The shapes and relative sizes of the various regions, layers, and elements illustrated in the figures are exemplary only and can vary depending on the manufacturing techniques used to produce the structures and the intended technical effects. The same reference numerals in different figures denote the same or similar elements.
[0058] As an aspect of the present application, the present application provides a general synthesis method of medium-entropy / high-entropy alloy nanoparticles, comprising the following steps:
[0059] 1) Dissolving three or more metal precursor salts in deionized water according to the required molar ratio, and performing ultrasonic treatment until complete dissolution to obtain a metal precursor solution A;
[0060] 2) Adding polyvinylpyrrolidone as a stabilizer to the solution A and stirring uniformly;
[0061] 3) Slowly adding a 0.3-0.5M sodium borohydride solution as a reducing agent to the solution A under stirring to form a reaction liquid B;
[0062] 4) Reacting the reaction liquid B at a constant temperature of 60-80℃ for 4-5 hours to form a uniform nanoparticle colloid;
[0063] 5) Centrifuging the nanoparticle colloid, washing 3-5 times with an equal volume of anhydrous ethanol and deionized water mixture, removing impurities, and vacuum freeze-drying for 8-12 hours to obtain black powder alloy nanoparticles.
[0064] The medium-entropy / high-entropy alloy nanoparticles prepared by the present application have a single-phase crystal structure, and each metal element is uniformly distributed in the crystal in the form of a solid solution; the crystal structure is face-centered cubic (FCC) or body-centered cubic (BCC); the particle size ranges from 2 to 10 nm and is uniformly distributed; and the metal elements are highly uniformly distributed in the particles without obvious agglomeration or segregation.
[0065] In the present application, "high entropy" refers to a configurational entropy S greater than or equal to 1.5R, and "medium entropy" refers to a configurational entropy S between 1.0R and 1.5R. R is the molar gas constant. Configurational entropy can effectively measure the degree of disorder and mixing of the system, and the higher the entropy value, the more stable the multi-element solid solution structure in the system, which is conducive to the formation of a stable and uniform single-phase structure.
[0066] According to some embodiments of the present application, in step 1), the required molar ratio refers to a molar ratio of 5-40%. For example, the medium-entropy / high-entropy alloy nanoparticles can contain the following five metal elements:
[0067] 5%-40% platinum (Pt);
[0068] 5%-40% copper (Cu);
[0069] 5%-40% silver (Ag);
[0070] 5%-40% cobalt (Co);
[0071] 5%-40% nickel (Ni).
[0072] According to some embodiments of the present application, the medium-entropy or high-entropy alloy nanoparticles include, but are not limited to, PtCuAg, PtCoNi, PtCoNiCu, PtPdCuAgZn.
[0073] According to some embodiments of the present application, in step 1), the metal precursor salt includes at least three of platinum salt, copper salt, silver salt, cobalt salt, nickel salt, and zinc salt.
[0074] According to some embodiments of the present application, in step 1), the platinum salt is K2PtCl4; the palladium salt is K2PdCl4; the copper salt is CuCl2; the silver salt is AgNO3; the cobalt salt is CoCl2; the nickel salt is NiCl2; and the zinc salt is ZnCl2.
[0075] According to some embodiments of the present application, in step 2), the concentration of polyvinylpyrrolidone is 1-5 mg / mL.
[0076] According to some embodiments of the present application, in step 3), the dropping speed of sodium borohydride is 0.5-1 mL / min.
[0077] According to some embodiments of the present application, in step 5), the centrifugal speed is 7000-9000 rpm, and the time is 8-12 min.
[0078] As another aspect of the present application, the medium-entropy / high-entropy alloy nanoparticles prepared by the above-mentioned preparation method are applied in the hydrogen evolution reaction of water electrolysis.
[0079] Preferably, the evaluation method of the catalytic performance of the medium-entropy / high-entropy alloy nanoparticles in the hydrogen evolution reaction of water electrolysis includes the following steps:
[0080] 1) Catalyst ink preparation:
[0081] The alloy nanoparticles are dispersed in a mixed solvent of isopropyl alcohol and water, and an appropriate amount of Nafion (5 wt.%) is added as a binder, and ultrasonic is used to form a uniform catalyst ink;
[0082] 2) Electrode preparation:
[0083] The catalyst ink is drop-casted on a clean and dry carbon paper or glassy carbon electrode, and a working electrode is formed after drying;
[0084] 3) Electrochemical test:
[0085] Linear sweep voltammetry (LSV), chronoamperometry (E-t), electrochemical impedance spectroscopy (EIS) and other performance tests were carried out in 0.5M H2SO4 or 1.0M KOH electrolyte saturated with N2, using a three-electrode system (Hg / HgO or Hg / Hg2SO4, platinum wire as the counter electrode, and the working electrode as the alloy-supported electrode).
[0086] Example 1
[0087] The embodiment provides a preparation method of a five-element high-entropy alloy nanoparticle catalyst (the metal components of which are platinum, copper, silver, cobalt and nickel), which comprises the following steps:
[0088] 1) precursor configuration:
[0089] The following metal salts are weighed:
[0090] 0.1 mmol K2PtCl 4( about 41.6 mg
[0091] 0.1 mmol CuCl2 (about 13.5 mg)
[0092] 0.1 mmol AgNO3 (about 17.0 mg)
[0093] 0.1 mmol CoCl2·6H2O (about 23.8 mg)
[0094] 0.1 mmol NiCl2·6H2O (about 23.7 mg)
[0095] The above metal salts are sequentially added to 100 mL of deionized water, and treated in an ultrasonic cleaning instrument for 30 minutes until completely dissolved, to form a uniform and clear metal precursor solution A.
[0096] 2) reduction reaction:
[0097] 100 mg of polyvinylpyrrolidone (PVP, molecular weight ≈ 40,000, concentration 1-5 mg / mL) is added to solution A as a stabilizer, and magnetically stirred to fully dissolve; then 50 mL of 0.4M sodium borohydride (NaBH4) solution is slowly added to the system at a rate of 1 mL / min using a syringe pump.
[0098] During the dropwise addition process, the solution gradually changes color (finally black), and the system gradually generates nanoparticle colloids. After the dropwise addition is completed, stirring is continued for 10 minutes to form a uniform reaction mixture B.
[0099] 3) hydrothermal treatment:
[0100] The solution is heated to 78-82°C, and the heating time is 4h;
[0101] 4) Product extraction and drying:
[0102] After the reaction, the system was naturally cooled to room temperature. A high-speed centrifuge (8000 rpm, 10 min) was used to separate the precipitate, which was repeatedly washed 4 times with a mixture of anhydrous ethanol and deionized water in equal volumes to remove residual reactants;
[0103] Finally, the product was dried in a vacuum freeze-drying box for 10 hours to obtain black powder of PtCuAgCoNi high-entropy alloy nanoparticle catalyst.
[0104] The high-entropy alloy nanoparticle catalyst obtained in this example was subjected to electrochemical catalytic performance testing according to the following method, including the following steps:
[0105] 1) The catalyst was configured into an electrocatalyst ink using an equal volume ratio of isopropyl alcohol and water mixed solvent;
[0106] 2) Catalytic performance evaluation under acidic conditions: The electrocatalyst ink was drop-cast on carbon paper, and in a three-electrode system with N2-saturated 0.5M H2SO4 as the electrolyte, a mercury sulfate electrode as the reference electrode, and a Pt sheet as the counter electrode, the electrolytic cell was an H-type electrolytic cell; the hydrogen evolution activity of the electrocatalyst in the acidic environment was evaluated by polarization curve. The results are shown in Figure 4 At a current density of 10 mA cm -2 , the overpotential of the PtCuAgCoNi catalyst was 12 mV, which was smaller than that of the Pt / C catalyst (33 mv), and the PtCuAgCoNi catalyst had excellent HER catalytic activity in acidic solution, and the overpotential did not decrease significantly after 10000 cv cycles, showing excellent durability, and the results are shown in Figure 4 .
[0107] Figure 1 is the TEM image and diffraction pattern of the high-entropy alloy nanoparticle electrocatalyst prepared in Example 1;
[0108] Figure 2 is the high-resolution EDS element mapping of the high-entropy alloy nanoparticle electrocatalyst prepared in Example 1;
[0109] Figure 3 is the XRD pattern and XPS pattern of the high-entropy alloy nanoparticle obtained by the preparation method of this example 1;
[0110] Figure 4 is the electrochemical performance of the electrocatalyst obtained by the preparation method of this example 1 and Pt / C (linear sweep voltammetry curve of hydrogen evolution reaction under acidic conditions)
[0111] Figure 5is a stability test of the electrocatalyst obtained by the preparation method of embodiment 1, LSV graphs before and after 10000 cv cycles.
[0112] Example 2
[0113] A preparation method of a ternary medium-entropy alloy nanoparticle (the metal components of which are platinum, copper, and silver) catalyst, comprising the following steps:
[0114] 1) Precursor configuration:
[0115] The following three kinds of metal precursor salts are weighed:
[0116] 0.1 mmol K2PtCl4 (about 41.6 mg)
[0117] 0.1 mmol CuCl2 (about 13.5 mg)
[0118] 0.1 mmol AgNO3 (about 17.0 mg)
[0119] The above metal salts are sequentially added to 100 mL of deionized water and treated in an ultrasonic cleaning instrument for 30 minutes until completely dissolved, to obtain a transparent and uniform metal precursor solution A;
[0120] 2) Reduction reaction:
[0121] 100 mg of polyvinylpyrrolidone (PVP, molecular weight about 40,000) is added to the solution A as a stabilizer and magnetically stirred to fully dissolve; then a 50 mL 0.4M sodium borohydride (NaBH4) solution is slowly added at a rate of 1 mL / min using a syringe pump;
[0122] During the dropwise addition process, the solution color gradually darkens and finally becomes black, and nanoparticle colloids are formed in the system. After the dropwise addition is completed, stirring is continued for 10 minutes to form a uniform reaction mixture B;
[0123] 3) Hydrothermal treatment:
[0124] The mixture B is heated to 60-82℃ in a constant-temperature water bath, and maintained for 4 hours to promote the formation and stability of the nanoparticle crystal structure.
[0125] 4) Product extraction and drying:
[0126] After the reaction is completed, the system is naturally cooled to room temperature. A high-speed centrifuge (8000 rpm, 10 min) is used to recover the precipitate, which is washed 4 times with an equal volume of anhydrous ethanol and deionized water mixture to remove residual reactants and impurities; the obtained product is dried in a vacuum freeze-drying box for 10 hours to obtain a black powder of the PtCuAg ternary medium-entropy alloy nanoparticle catalyst.
[0127] The obtained nanoparticles were tested for catalyzing the hydrogen evolution reaction of water electrolysis, and exhibited good electrocatalytic performance in acidic medium.
[0128] Figure 6 is the XRD pattern of the PtCuAg entropic alloy nanoparticles prepared in this Example 2.
[0129] Figure 7 is the high-resolution EDS element mapping of the alloy catalyst prepared in this Example 2, showing that the three elements Pt, Cu, and Ag are highly uniformly distributed in the particles;
[0130] Figure 8 is the transmission electron microscope (TEM) image of the PtCuAg entropic alloy nanoparticles prepared in this Example 2.
[0131] Example 3
[0132] This example provides a preparation method of a quaternary entropic alloy nanoparticle catalyst (whose metal components are platinum, cobalt, nickel, and copper), comprising the following steps:
[0133] 1) Precursor configuration:
[0134] The following four kinds of metal precursor salts were weighed:
[0135] 0.1 mmol K2PtCl4(approximately 41.6 mg)
[0136] 0.1 mmol CoCl2·6H2O (about 23.8 mg)
[0137] 0.1 mmol NiCl2·6H2O (about 23.7 mg)
[0138] 0.1 mmol CuCl2(approximately 13.5 mg)
[0139] The above metal salts were sequentially dissolved in 100 mL of deionized water, and treated in an ultrasonic cleaning instrument for 30-60 minutes until a clear and uniform precursor solution A was formed;
[0140] 2) Reduction reaction:
[0141] 100 mg of polyvinylpyrrolidone (PVP, molecular weight about 40,000) was added to the solution A as a stabilizer, and stirred to dissolve completely; then 50 mL of 0.4M sodium borohydride (NaBH4) solution was slowly added at a rate of 1 mL / min using a syringe pump;
[0142] During the dropping process, the color of the solution gradually changed from light purple to dark gray, and finally black, and the nanoparticles colloid began to form in the system. After the dropping process was completed, the stirring was continued for 10 minutes to form a uniform reaction mixture B;
[0143] 3) Hydrothermal treatment:
[0144] Reaction mixture B was heated in a 60-82°C water bath for 4 hours to promote the crystallization and uniform nucleation of alloy particles;
[0145] 4) Product extraction and drying:
[0146] After the reaction was completed, the system was naturally cooled to room temperature. High-speed centrifugation (8000 rpm, 10 min) was used to collect the precipitate, which was washed 4 times with a mixed solution of anhydrous ethanol and deionized water (volume ratio 1:1) to remove residual reactants and impurities; finally, the obtained precipitate was dried in a vacuum freeze-drying box for 10 hours to obtain black powder PtCoNiCu quaternary entropy alloy nanoparticle catalyst.
[0147] Tests showed that the obtained nanoparticle structure was uniform, with small particle size, and exhibited good electrocatalytic activity and long-term stability in the electrolytic water hydrogen evolution reaction;
[0148] Figure 9 The XRD pattern of the PtCoNiCu alloy nanoparticles obtained in this embodiment 3 showed that it was a single-phase FCC structure;
[0149] Figure 10 The transmission electron microscope (TEM) image of the PtCoNiCu alloy nanoparticles obtained in this embodiment 3 showed that the average particle size was about 2-10 nm;
[0150] Figure 11 The EDS element mapping image of the alloy particles of the PtCoNiCu alloy nanoparticles obtained in this embodiment 3 showed that the four elements Pt, Co, Ni, and Cu were uniformly distributed in the particles;
[0151] Comparative Example 1
[0152] Example 1 was repeated, except that in step 2), the concentration of polyvinylpyrrolidone was 0.4 mg / mL.
[0153] After detection, the obtained product black powder PtCuAgCoNi high-entropy alloy nanoparticle catalyst exhibited a current density of 10 mA cm -2 The overpotential of the PtCuAgCoNi catalyst was 54 mV under a current density of 10 mA cm. That is, the concentration of polyvinylpyrrolidone was too low to well control the morphology, resulting in a large amount of catalyst aggregation and a significant decrease in the electrocatalytic performance of the product.
[0154] Comparative Example 2
[0155] Example 1 is repeated, except that in step 2), the concentration of polyvinylpyrrolidone is 8 mg / mL.
[0156] After testing, the obtained product, a black powder-like PtCuAgCoNi high-entropy alloy nanoparticle catalyst, was found to be 10 mA / cm². -2 At the current density (normalized to the electrode geometry), the overpotential of the PtCuAgCoNi catalyst is 46 mV. This means that if the polyvinylpyrrolidone concentration is too high, the polyvinylpyrrolidone adheres to the catalyst surface, making it difficult to clean during the washing process. This also results in a low product yield, and excessive amounts can significantly reduce the electrocatalytic performance of the product.
[0157] Comparative Example 3
[0158] Repeat Example 1, except that in step 3), the sodium borohydride is dropped at a rate of 0.2 mL / min.
[0159] After testing, the obtained product, a black powder-like PtCuAgCoNi high-entropy alloy nanoparticle catalyst, was found to be 10 mA / cm². -2 At the given current density (normalized to the electrode geometry), the overpotential of the PtCuAgCoNi catalyst is 34 mV. This means that a low dropping rate of the sodium borohydride will also lead to a significant decrease in the electrocatalytic performance of the product.
[0160] Comparative Example 4
[0161] Repeat Example 1, except that in step 3), the sodium borohydride is dropped at a rate of 3 mL / min.
[0162] After testing, the obtained product, a black powder-like PtCuAgCoNi high-entropy alloy nanoparticle catalyst, was found to be 10 mA / cm². -2 At the given current density (normalized to the electrode geometry), the overpotential of the PtCuAgCoNi catalyst is 28 mV. This means that an excessively high dropping rate of the sodium borohydride can lead to elemental segregation, resulting in a significant decrease in the electrocatalytic performance of the product.
[0163] Figure 12 These are the electrochemical performance (linear sweep voltammetric curves of the hydrogen evolution reaction under acidic conditions) of the electrocatalysts prepared by four comparative example methods.
[0164] Figure 13The transmission electron microscope (TEM) image of the PtCoNiCuAg alloy nanoparticles obtained in the present comparative example 1 shows obvious agglomeration.
[0165] Figure 14 The XRD image and transmission electron microscope (TEM) image of the PtCoNiCuAg alloy nanoparticles obtained in the present comparative example 4 show obvious element segregation.
[0166] In summary, the test results of the present application show that, under a current density of 10 mA·cm -2 The overpotential of the alloy catalyst prepared in the present application can be less than 30 mV, with excellent HER activity and stability; the overpotential does not decrease significantly after 10000 cv cycles, showing excellent durability. The preparation method of the medium-entropy / high-entropy alloy nanoparticle catalyst provided in the present application is simple, controllable and highly versatile, the obtained material has good crystal structure and catalytic performance, is suitable for water electrolysis and other green energy conversion fields, and has important scientific research and industrial promotion value.
[0167] Obviously, the above examples of the present application are only examples for clearly illustrating the present application, and are not intended to limit the embodiments of the present application. Based on the above description, other different forms of changes or variations can be made by those of ordinary skill in the art. It is impossible to enumerate all the embodiments here. Any obvious changes or variations derived from the technical solutions of the present application still fall within the protection scope of the present application.
Claims
1. A general synthesis method of medium entropy / high entropy alloy nanoparticles, characterized in that, The method comprises the following steps: 1) Dissolve three or more metal precursor salts in deionized water according to the required molar ratio, and ultrasonic treatment until completely dissolved to obtain a metal precursor solution A; 2) Add polyvinylpyrrolidone as a stabilizer to solution A and stir until uniform; 3) Under stirring conditions, slowly add 0.3-0.5M sodium borohydride solution as a reducing agent to solution A to form reaction liquid B; 4) React the reaction liquid B at 60-80°C for 4-5 hours to form a uniform nanoparticle colloid; 5) Centrifuge the nanoparticle colloid, wash with an equal volume of anhydrous ethanol and deionized water mixture for 3-5 times, remove impurities, and vacuum freeze dry for 8-12 hours to obtain black powder alloy nanoparticles.
2. The general synthetic method according to claim 1, wherein: In step 1), the ultrasonic treatment time is 30-60 min.
3. The general synthetic method according to claim 1, wherein: In step 1), the required molar ratio refers to a molar ratio of 5-40%.
4. The general synthetic method of claim 1, wherein: In step 1), the metal precursor salt includes at least three of platinum salt, copper salt, silver salt, cobalt salt, nickel salt, and zinc salt.
5. The general synthetic method according to claim 1, wherein: In step 1), the platinum salt is K2PtCl4; the palladium salt is K2PdCl4; the copper salt is CuCl2; the silver salt is AgNO3; the cobalt salt is CoCl2; the nickel salt is NiCl2; and the zinc salt is ZnCl2.
6. The general synthetic method according to claim 1, wherein: The medium-entropy or high-entropy alloy nanoparticles include but are not limited to PtCuAg, PtCoNi, PtCoNiCu, PtPdCuAgZn.
7. The general synthetic method according to claim 1, wherein: In step 2), the polyvinylpyrrolidone concentration is 1-5 mg / mL.
8. The general synthetic method of claim 1, wherein: In step 3), the sodium borohydride dropwise rate is 0.5-1 mL / min.
9. The general synthetic method of claim 1, wherein: In step 5), the centrifugal speed is 7000-9000 rpm, and the time is 8-12 min.
10. The application of the medium-entropy / high-entropy alloy nanoparticles prepared by any one of the preparation methods in claims 1-9 in electrolytic water hydrogen evolution reaction; Preferably, the evaluation method of the catalytic performance of the medium-entropy / high-entropy alloy nanoparticles in electrolytic water hydrogen evolution reaction comprises the following steps: 1) Catalyst ink preparation: Disperse the alloy nanoparticles in a mixed solvent of isopropyl alcohol and water, add an appropriate amount of Nafion (5 wt.%) as a binder, and ultrasonic to form a uniform catalyst ink; 2) Electrode preparation: Drop the catalyst ink on a clean and dry carbon paper or glassy carbon electrode, and dry to form a working electrode; 3) Electrochemical test: In N2-saturated 0.5M H2SO4 or 1.0M KOH electrolyte, a three-electrode system is used: Hg / HgO or Hg / Hg2SO4, platinum wire as the counter electrode, and the working electrode as the alloy-loaded electrode, to perform linear sweep voltammetry, chronopotentiometry, and electrochemical impedance spectroscopy performance tests.
Citation Information
Cited By
Preparation method of non-noble metal medium / high-entropy alloy aerogel electrocatalytic material
CN121556076A